BIOLOGICAL LEARNING ADAPTATION DURING THE COVID-19 PANDEMIC PERIOD IN PONOROGO 1 PUBLIC HIGH SCHOOL - NAWAWI NAWAWI; SUKARDI SUKARDI; ISRA' INDAR HANDAYANI (Acitya: Journal of Teaching and Education, 2021)
This study aims to see an overview of the adaptations that students have made to learning during the Covid-19 pandemic in biology subjects at Ponorogo 1 Public High School. The research method used is a descriptive quantitative method with data collection carried out through online questionnaires using the google formula to 361 students of Ponorogo 1 Public High School from Class X, XI, and XII MIPA related to the implementation of biology learning. Based on online questionnaires, 67.31% of respondents had difficulty understanding the learning material because they did not meet directly with the teacher so that 50.14% of respondents tried to always come on time to participate in online learning. The application that mostly like by 68.70% of respondents is google classroom. While 93.91% of respondents can apply independent learning, and 77.56% of respondents feel happy with online learning.